Perilaku Masturbasi di Kalangan Remaja dan Kaitannya dengan Self-Concept - Dodikrisno E Manery; Abdul M Ukratalo; Edwin Buranga; Arief Rahman S Kaliky (STIKes Ibnu Sina Ajibarang, 2025)
Masturbation is a common aspect of sexual development in adolescents and plays a role in identity exploration and the formation of self-concept. Adolescence represents a critical developmental phase during which individuals seek to understand their identity, including their body and sexuality. Within a psychosocial context, masturbation may contribute positively to self-concept development when supported by a healthy understanding and an inclusive environment. However, social pressures, religious norms, and cultural values that prohibit or stigmatize masturbation often generate internal conflict, influencing adolescents’ self-perception. The resulting negative self-concept may lead to feelings of shame, guilt, stress, and adverse impacts on mental health. This study aims to examine masturbation behavior among adolescents and its association with negative self-concept. The method employed is a literature review, utilizing both scholarly books and peer-reviewed journal articles. Data collection techniques included gathering literature sources, reading and sorting data, note-taking, identifying relevant findings, and validating the information to support analytical interpretation. Findings indicate that adolescents with a positive self-concept are more capable of accepting their sexual behavior, including masturbation, without excessive guilt or shame. Conversely, those with a negative self-concept are more likely to experience internal conflict that compromises psychological well-being. Factors such as family support, open sexual education, and media influence play a significant role in shaping the relationship between masturbation and self-concept. Comprehensive sexual education can enhance adolescents’ understanding of their bodies and sexuality, thereby reducing stigma and fostering a positive self-concept. In contrast, restrictive and stigmatizing environments tend to worsen self-image and may contribute to anxiety and depression.